Tension force causes cell cycle arrest at G2/M phase in osteocyte-like cell line MLO-Y4. Issue 2 (February 2023) - Shimizu, Natsuo; Fujiwara, Kyoko; Mayahara, Kotoe; Motoyoshi, Mitsuru; Takahashi, Tomihisa
Abstract: Bone remodelling is the process of bone resorption and formation, necessary to maintain bone structure or for adaptation to new conditions. Mechanical loadings, such as exercise, weight bearing and orthodontic force, play important roles in bone remodelling. During the remodelling process, osteocytes play crucial roles as mechanosensors to regulate osteoblasts and osteoclasts. However, the precise molecular mechanisms by which the mechanical stimuli affect the function of osteocytes remain unclear. In the present study, we analysed viability, cell cycle distribution and gene expression pattern of murine osteocyte-like MLO-Y4 cells exposed to tension force (TF). Cells were subjected to TF with 18% elongation at 6 cycles/min for 24 h using Flexcer Strain Unit (FX-3000). We found that TF stimulation induced cell cycle arrest at G2/M phase but not cell death in MLO-Y4 cells. Differentially expressed genes (DEGs) between TF-stimulated and unstimulated cells were identified by microarray analysis, and a marked increase in glutathione-S-transferase α (GSTA) family gene expression was observed in TF-stimulated cells. Enrichment analysis for the DEGs revealed that Gene Ontology (GO) terms and Kyoto Encyclopedia Genes and Genomes (KEGG) pathways related to the stress response were significantly enriched among the upregulated genes following TF. Consistent with these results, the production of reactive oxygen species (ROS) was elevated in TF-stimulated cells. Activation of the tumour suppressor p53, and upregulation of its downstream target GADD45A, were also observed in the stimulated cells. As GADD45A has been implicated in the promotion of G2/M cell cycle arrest, these observations may suggest that TF stress leads to G2/M arrest at least in part in a p53-dependent manner.